Theoretical analysis of video pulses distribution in bovine mammary - Торчук, Михаил Васильевич (Technology audit and production reserves, 2014)
The preservation of newborn calves particularly in the first days of life is being influenced by the amount of immunoglobulins in colostrum and milk of cows. Immunoglobulins perform a leading role in humoral immunity, their level reflects the functional activity of B-lymphocytes. Recently in human and veterinary medicine electromagnetic methods are gaining attention which allow to improve immunoglobulins in colostrum and milk cows. Thus in the article the theoretical analysis was made of the interaction of electric field pulses with a mammary gland calved cows. The obtained results allow us to investigate the distribution of pulsed electric field in the mammary gland and determine the parameters of pulsed radiation (pulse amplitude, frequency and pulse repetition period; exposure value) to increase immunoglobulins LgG and LgM. Increase in immunoglobulins in colostrum and milk allows to boost immunity in order to preserve the newborn calves and reduce the cost of their treatment